2004
DOI: 10.1089/1084978041979625
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Therapeutic Tumor Response Using <SUP>99m</SUP>Tc-Ethylenedicysteine-Glucosamine

Abstract: Purpose: The aim of this study was to evaluate 99m Tc-ethylenedicysteine-glucosamine (EC-DG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
0
15
0
2
Order By: Relevance
“…Îïóõîëè íèç-êîé ñòåïåíè çëîêà÷åñòâåííîñòè (low-grade) õàðàêòåðèçî-âàëèñü ïîíèaeåííûì ìåòàáîëèçìîì ãëþêîçû, à îïóõîëè âûñîêîé ñòåïåíè çëîêà÷åñòâåííîñòè (high grade) -ãè-ïåðìåòàáîëèçìîì [55]. Ñêîðîñòü ãëèêîëèçà â ãëèîìàõ, îïðåäåëÿåìàÿ ìåòîäîì ÏÝÒ ñ 18 F-ÔÄÃ, áîëåå òî÷íî îòðà-aeàåò ñòåïåíü çëîêà÷åñòâåííîñòè, ÷åì äàííûå ÌÐÒ èëè ÊÒ [93].…”
Section: âîçìîAeíîñòè ïýò ñ [unclassified
“…Îïóõîëè íèç-êîé ñòåïåíè çëîêà÷åñòâåííîñòè (low-grade) õàðàêòåðèçî-âàëèñü ïîíèaeåííûì ìåòàáîëèçìîì ãëþêîçû, à îïóõîëè âûñîêîé ñòåïåíè çëîêà÷åñòâåííîñòè (high grade) -ãè-ïåðìåòàáîëèçìîì [55]. Ñêîðîñòü ãëèêîëèçà â ãëèîìàõ, îïðåäåëÿåìàÿ ìåòîäîì ÏÝÒ ñ 18 F-ÔÄÃ, áîëåå òî÷íî îòðà-aeàåò ñòåïåíü çëîêà÷åñòâåííîñòè, ÷åì äàííûå ÌÐÒ èëè ÊÒ [93].…”
Section: âîçìîAeíîñòè ïýò ñ [unclassified
“…Our previous work demonstrated that tumor uptake of 99m Tc-EC-DG is via a glucose-mediated process [16,70]. One reason may be that the molecule (EC-DG) has multiple key structural position(s), such as positions 2 and 6 for Dglucosamine and the two COO-arms and two thiol (SH) locations for EC.…”
Section: Assessment Of Metabolic Imagingmentioning
confidence: 99%
“…This blockade in the pathway causes an inability for further metabolism and thus remains in the cell. (13,14) In this study, we introduce a novel Gd-based contrast agent for cancer cell imaging. Our study foucosed on the expolation of the glucose transport system in order to Incorporate Gd conjugated with glucose (Gd-DTPA-DG) into the cancer cells.…”
Section: Iintroductionmentioning
confidence: 99%